Evaluation of 'see-see and treat' strategy and role of HIV on cervical cancer prevention in Uganda - Mutyaba, Twaha; Mirembe, Florence; Sandin, Sven; Weiderpass, Elisabete (Reproductive Health, 2010)
There is scant information on whether Human Immunodeficiency Virus (HIV) seropositivity has an influence on the outcome of treatment of precancerous cervical lesions using cryotherapy. We studied the prevalence of cervical abnormalities detectable by visual inspection and cervical lesions diagnosed by colposcopy according to HIV serostatus and described the outcomes of cryotherapy treatment. Trained nurses examined women not previously screened for cervical cancer using visual inspection with acetic acid (VIA) and Lugol's iodine (VILI) in two family planning/post natal clinics in Kampala, Uganda, from February 2007 to August 2008. Women with abnormal visual inspection findings were referred for colposcopic evaluation and HIV testing. Women with precancerous cervical lesions detected at colposcopy were treated mainly by cryotherapy, and were evaluated for treatment outcome after 3 months by a second colposcopy.
Keywords: Research evaluation; Treat' strategy; HIV; Cervical cancer; Uganda